Association of Placental Mesenchymal Dysplasia With a Live Female Fetus and Complete Hydatidiform Mole: Report of a Challenging Case Confirmed by Molecular Genotyping Analysis. (1st May 2022) - Hamard, Aymeric; Heitzmann, Anne; Ceccaldi, Claire; Descriaud, Céline; Mauduit, Claire; Gaillot-Durand, Lucie; Hajri, Touria; Massardier, Jérôme; Vinas, Roselyne; Allias, Fabienne
Abstract : Placental mesenchymal dysplasia (PMD) and complete hydatidiform mole (CHM) with a coexisting fetus are 2 rare placental abnormalities characterized by lacunar placenta and presence of an embryo on ultrasound examination. We report the case of a 34-yr-old woman referred at 32.6 weeks of gestation because of a multicystic placenta. A caesarean section was performed at 39.1 weeks of gestation giving birth to a 2905 g normal female infant. Pathological examination revealed macroscopic and microscopic morphological, and immunohistological features of PMD in the main placenta, and features of CHM in a separate placental mass. Fluorescent in situ hybridization and molecular genotyping analyses showed diandric diploidy in the CHM component and androgenetic/biparental mosaicism in the PMD component, confirming the association of PMD and CHM with a live infant. There was no progression to gestational trophoblastic neoplasia during follow-up for the mother, or any sign of Beckwith-Wiedemann syndrome or hepatic tumor in the child.